2021
DOI: 10.1111/cns.13767
|View full text |Cite
|
Sign up to set email alerts
|

18F‐fluorodeoxy‐glucose positron emission tomography pattern and prognostic predictors in patients with anti‐GABAB receptor encephalitis

Abstract: Aims To identify the metabolic pattern and prognostic predictors in anti‐gamma‐aminobutyric‐acid B (GABAB) receptor encephalitis using 18F‐fluorodeoxy‐glucose positron emission tomography (18F‐FDG‐PET). Methods Twenty‐one patients diagnosed anti‐GABAB receptor encephalitis who underwent 18F‐FDG‐PET at first hospitalization were retrospectively reviewed. 18F‐FDG‐PET images were analyzed in comparison with controls. Further group comparisons of 18F‐FDG‐PET data were carried out between prognostic subgroups. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
4
0
15
Order By: Relevance
“…Patients with increased metabolism in the MTL tend to have poor outcomes after a median follow-up of 33 months. 31 In a study of five patients with anti-GABA B receptor encephalitis, three patients showed abnormalities on PET, including two temporal hypermetabolism and one cortical hypometabolism. 32 Another patient with small cell lung cancer who presented with 3 weeks of progressive seizures, memory impairment, and behavioral disorder was diagnosed with anti-GABA B receptor encephalitis.…”
Section: Anti-gamma-aminobutyric Acid Receptor Encephalitismentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with increased metabolism in the MTL tend to have poor outcomes after a median follow-up of 33 months. 31 In a study of five patients with anti-GABA B receptor encephalitis, three patients showed abnormalities on PET, including two temporal hypermetabolism and one cortical hypometabolism. 32 Another patient with small cell lung cancer who presented with 3 weeks of progressive seizures, memory impairment, and behavioral disorder was diagnosed with anti-GABA B receptor encephalitis.…”
Section: Anti-gamma-aminobutyric Acid Receptor Encephalitismentioning
confidence: 99%
“…Group analysis also confirmed MTL hypermetabolism and frontal–parietal hypometabolism (Figure 3). Patients with increased metabolism in the MTL tend to have poor outcomes after a median follow‐up of 33 months 31 . In a study of five patients with anti‐GABA B receptor encephalitis, three patients showed abnormalities on PET, including two temporal hypermetabolism and one cortical hypometabolism 32 .…”
Section: Visual Assessment Of Brain 18f‐fdg‐pet Metabolic Patterns By...mentioning
confidence: 99%
“…Die zerebrale MRT mit T1-, T2, FLAIR-und diffusionsgewichteten Sequenzen ist Teil der Basisdiagnostik bei Verdacht auf eine LE [16,20,38], wobei nur die FLAIR-Sequenz Bestandteil der o. g. diagnostischen Kriterien ist [16]. Initial zeigen etwa 50-75% der Patienten mit limbischer Enzephalitis eine unilaterale oder bilaterale Hyperintensität in der T2/FLAIR-MRT [13,41,46,47], meist ohne Kontrastmittelaufnahme. Mittels Volumetrie des Hippocampus und hippocampler Subfelder sowie voxelbasierter Volumetrie der grauen Substanz anhand T1w-MRT konnten auch strukturelle Veränderungen (Atrophie) nachgewiesen werden, die möglicherweise als Hinweise für das Auftreten und Fortschreiten eines Neuronenverlustes dienen können [41].…”
Section: Zerebrale Mrtunclassified
“…2, Abb. 3) [47,48,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80]. Dabei kann sowohl ein Hyper-, seltener auch ein Hypometabolismus mesiotemporal auftreten [76,77,81].…”
Section: Zerebrale Fdg-petunclassified
See 1 more Smart Citation